Ultrafine-grained Al-Mg-Zr alloy processed by shear-assisted extrusion with high thermal stability. (September 2020) - Croteau, Joseph R.; Jung, Jae-Gil; Whalen, Scott A.; Darsell, Jens; Mello, Austin; Holstine, Dallas; Lay, Kylee; Hansen, Michael; Dunand, David C.; Vo, Nhon Q.
Abstract: Shear-assisted processing and extrusion (ShAPE) is used to consolidate Al-4.2Mg-1.6Zr-0.25Si-0.1Fe (wt.%) powders. The extruded alloy exhibits: (i) near-zero porosity; (ii) an attractive combination of tensile yield strength ( 220 MPa), ultimate strength (330 MPa) and elongation (>20%); and (iii) excellent thermal stability at 400 °C. The ultra-fine grain size in the gas-atomized powders – created and stabilized by primary L12 -Al3 Zr submicron precipitates - is maintained after consolidation and subsequent exposure at 400 °C, contributing twice as much to strength as Mg in solid-solution. Electron microscopy reveals the microstructure of the L12 -Al3 Zr precipitates, and other precipitates (Mg2 Si and Al3 Fe) and dispersoids (oxides). Graphical abstract: Image, graphical abstract